Implementation of Moral Religion in Education in Majalengka, Indonesia - Sarbini (GoAcademica Research & Publishing, 2020)
This article seeks to explain how the implementation of moral education is presented at elementary level schools in the midst of community conditions that have changed from an agricultural community to an industrialized society. This study aims to understand how the cognition, affection, and psychomotor aspects of students in the implementation of religious moral values ​​are presented in schools. This research uses qualitative methods with a descriptive approach. Data collection techniques taken were observation, interviews with students from elementary level schools in Cidenok Village, Sumberjaya District, Majalengka Regency. This study found that the moral values ​​of religion presented in schools are still transfer of knowledge and religion in the cognitive aspects, only a small part is in the affective and psychomotor aspects. Second, the socio-economic conditions of the family are part of the background for moral value education which is not optimally absorbed into the affective and psychomotor aspects. Third, the condition of the social environment has a big role in shaping student orientation, where the moral values ​​of religion do not become the control lines for students in carrying out social interactions in society. This study concludes that the implementation of religious moral values ​​in education in schools has a clash with family awareness in supporting education, learning models that are still limited to transfer of knowledge, and the social environment of society.